Economía Urbana y Expansión Metropolitana Estrategias de localización de los grupos empresariales en la Región Metropolitana de Belém - Veloso dos Santos, Tiago (2022)
In the context of urban expansion in the Metropolitan Region of Belém (MRB), we analyze the logic of action of certain business groups and the relationship with the trend of spreading of the urban-metropolitan fabric nucleated by the city of Belém. The analysis stems from the emergence of supermarket retail groups as an expression of a metropolitan economy organized around the modern tertiary sector, especially commerce and services, of which two business groups stand out, “Líder” and “Y. Yamada". Despite of acting to intensify the logic of metropolitan expansion, the groups act in a strategically different way in terms of locational choices. The methodological path of the research is comprised of three stages: systematic literature review, survey and document analysis, systematic field observations with subsequent production of cartography of the observed processes and statistical data collected.